Pendampingan Usaha Mikro Kecil Menengah (UMKM) melalui Pemanfaatan Platform Digital di Desa Tambang Besi - Sodiah, Sodiah; Fitri, Desrifa; Aziz, Suci Karlina; Nashikha, Nurul Latifatun; Mukni, Rahma Mutia; Sari, Ika Yulia; Bashori, Bashori (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IAIN Lhokseumawe, 2023)
This research aims to improve the skills and knowledge of Micro, Small, and Medium Enterprises (MSMEs) in Tambang Besi Village, focusing on the production and marketing of traditional snacks. With an emphasis on product diversification and the utilization of digital marketing, the research objectives encompass enhancing local economic growth, expanding market access, and preserving the authenticity of traditional flavors. The study employs a community engagement approach involving both faculty and students in mentoring activities. Data collection methods include interviews, observations, document analysis, and mentoring. The findings of the research are as follows: 1) The planning phase involves setting objectives and identifying the strengths and weaknesses of MSMEs. The implementation phase includes socialization, product creation, and promotion through social media. Evaluation is conducted through survey-interviews and social media analysis to measure the progress of MSMEs during the development period. 2) The addition of dumplings as a diversification effort has successfully aligned with the tastes of children and teenagers, enhancing the appeal of MSME products. The effective use of digital marketing through social media has increased product visibility, evident in the rise in likes, comments, and shares. 3) The mentoring activities also identified weaknesses, such as limited knowledge in marketing, insufficient skills in innovation, and restricted market access. Based on the research outcomes, it is recommended to continuously integrate innovative products following the latest food trends and strengthen digital marketing strategies. MSME participants should consistently receive guidance in managing and expanding market access while enhancing skills in utilizing social media.